2012
DOI: 10.1371/journal.ppat.1002896
|View full text |Cite
|
Sign up to set email alerts
|

CPSF6 Defines a Conserved Capsid Interface that Modulates HIV-1 Replication

Abstract: The HIV-1 genome enters cells inside a shell comprised of capsid (CA) protein. Variation in CA sequence alters HIV-1 infectivity and escape from host restriction factors. However, apart from the Cyclophilin A-binding loop, CA has no known interfaces with which to interact with cellular cofactors. Here we describe a novel protein-protein interface in the N-terminal domain of HIV-1 CA, determined by X-ray crystallography, which mediates both viral restriction and host cofactor dependence. The interface is highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
364
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(388 citation statements)
references
References 44 publications
23
364
1
Order By: Relevance
“…5), arguing that HIV-1 replication does not rely on the steadystate level of Tnpo3-CPSF6 complexes. These results agree with the model whereby cytoplasmically delocalized CPSF6 inhibits HIV-1 infectivity via premature engagement of the viral capsid (31,35). The antagonistic HIV-1 capsid-CPSF6 interaction is supported by a substantial weight of genetic evidence, and potential nuclear functions of CPSF6 as an HIV-1 host factor remain an intriguing possibility for further investigation (30-32, 34, 49, 50).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…5), arguing that HIV-1 replication does not rely on the steadystate level of Tnpo3-CPSF6 complexes. These results agree with the model whereby cytoplasmically delocalized CPSF6 inhibits HIV-1 infectivity via premature engagement of the viral capsid (31,35). The antagonistic HIV-1 capsid-CPSF6 interaction is supported by a substantial weight of genetic evidence, and potential nuclear functions of CPSF6 as an HIV-1 host factor remain an intriguing possibility for further investigation (30-32, 34, 49, 50).…”
Section: Resultssupporting
confidence: 85%
“…A surprising discovery that a CPSF6 deletion mutant lacking the RS domain can potently inhibit HIV-1 replication through direct binding to capsid provides for a link between Tnpo3 and a viral component (34,35).…”
mentioning
confidence: 99%
“…Although we and others have shown that TRN-SR2 directly interacts with HIV IN (18,19,27,38,39), the mechanism of action has been questioned (19,23,36,40,41). Especially reports on a set of HIV capsid mutations (e.g.…”
mentioning
confidence: 94%
“…CPSF6 is a cellular protein involved in splicing and polyadenylation of pre-mRNA that carries an RS domain at its C terminus. Because CPSF6 binds HIV CA (40), it has been suggested that TRN-SR2 depletion might result in cytoplasmic accumulation of CPSF6, which in turn might perturb viral uncoating through CPSF6-CA binding, leading to an indirect block in nuclear import and restricted HIV replication (36,40,41). Still, the cytoplasmic accumulation of CPSF6 after TRN-SR2 knockdown is not always observed (36,41).…”
mentioning
confidence: 99%
“…We and others have previously demonstrated that the small-molecule HIV-1-inhibitor PF74 prevents the binding of CPSF6 to HIV-1 capsid [6,17]. Because of the similar phenotypes observed for HIV-1-GFP infection when using BI-2 and PF74, we tested the ability CPSF6 to bind in vitro assembled HIV-1 CA-NC complexes in the presence of BI-2.…”
Section: Bi-2 Prevents the Binding Of Cpsf6 To In Vitro Assembled Hivmentioning
confidence: 97%